“Implementación de un sistema de generación de energía limpia por medio de sensores piezoeléctricos para la iluminación de la entrada del bloque b de la UTC Extensión La Maná”. - Caldaz Sarmiento, Marcos Eduardo (2022)
The energy generation through alternative sources has gained fields today, it is intended that in the future the processes of generating electrical energy are friendly to the environment and the environment, leaving behind the current ones such as hydroelectric, thermoelectric, nuclear, among others. others. This project deals with the study, analysis and implementation of an innovative system based on the production of electrical energy from piezoelectric materials and sensors. The project makes it possible to compensate for a lighting problem at the entrance to Block B of the Extension and at the same time investigate and collect information about the operation of the energy generation by the piezoelectric system. With these precedents, bibliographic information on the generation of piezoelectric energy was collected, the way in which the footsteps of people entering or leaving the university establishment were used to produce electrical energy and power the lighting of the university was also analyzed. the front of the Technical University of Cotopaxi. The tests and results show us that the project provides a common benefit, a new energy generation alternative with energy savings, in turn contributing to the University's research and care for its visual and environmental ecosystem.